The effect of an educational program based on cognitive expansion skills in developing metacognitive thinking skills through biology for 7th graders in Lattakia city - رغداء نصور; ميساء حمدان; عائشة كادونة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aims of the research is to study the effect of using cognitive expansion skills in developing metacognitive thinking skills among seventh graders in biology in the city of lattakia. The researcher chose a unit from the biology book for the seventh grade; then this unit was designed to suit the skills of expanding perception, it prepared a measure of metacognitive skills, and then it chose a sample of seventh graders in the city of lattakia; Then the sample was divided into two groups (experimental and control). The researcher verified the equivalence of the two groups through the pre-application of the metacognitive skills scale, then the experimental group studied the educational unit using cognitive expansion skills, and the control group studied the same unit using the usual methods, then applied the skills scale afterwards, and the researcher compared between the experimental and control groups, and the results came on as follows: There is a statistically significant difference between the mean scores of the students of the two groups (experimental and control) in the post application of the experimental group. The research ended with a set of conclusions and suggestion, such as the necessity of paying attention to training teachers to use thinking skills in biology.